Nadzwyczajni dwudziestoletni — rzecz o najmłodszych profesorach zwyczajnych na Wydziale Prawa Uniwersytetu Wrocławskiego w latach 1811−1945 - Dolata, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The youngest German scholars working at the Faculty of Law at the University of Wrocław in the years 1811–1945 who received the title of an ordinary professor before their thirtieth birthday, are discussed in the article. On the basis of an analysis of their CVs, it can be argued that such rapid and spectacular academic careers were more frequent in the nineteenth century, and a lot less frequent in subsequent years. However, an appointment to ordinary full professorship for scholars after 30 years of age was not uncommon. The vast majority of scholars received this honour just between 31 and 40 years of age. After the age of 40, the number of professorial appointments of scholars rapidly declined. Actually, exceptional cases included nominations for professorship to scholars over 50 there were only few such cases.Moreover, the article discusses the factors affecting the scholars as the ordinary full professors, it draws attention to a number of rights and privileges connected with being an ordinary professor. Using the example of the youngest professors of law, the author also referres to the then academic view of German scholars who regarded the Silesian Alma Mater as a kind of a “waiting room” before leaving for a better university.
Keywords: Uniwersytet Wrocławski; Wydział Prawa Uniwersytetu Wrocławskiego w latach 1811–1945; wykładowca prawa na Uniwersytecie Wrocławskim; niemieccy profesorowie prawa